New insights on Bjerkandera (Phanerochaetaceae, Polyporales) in the Neotropics with description of Bjerkandera albocinerea based on morphological and molecular evidence - Motato-Vásquez, Viviana (2020)
Bjerkandera is one of the few poroid genera in the Phanerochaetaceae family known to date. The genus has a worldwide distribution and is characterized by effused-reflexed, pileate basidiomata with a pale cream to smoky or mouse grey hymenophore that becomes darker when dried, and a monomitic hyphal structure with clamped generative hyphae. Morphological and phylogenetic studies have traditionally accepted only two species in the genus, B. adusta (generic type) and B. fumosa, both described from temperate Europe. Recently, three additional species, B. atroalba, B. centroamericana and B. mikrofumosa were described from the Neotropics. While studying polypores in the Yungas forests of northwest Argentina and the Atlantic Forest of southeast Brazil, several specimens of Bjerkandera were gathered. A comparative morphological study revealed that some of these specimens do not correspond to any of the known species in the genus. This study aimed to propose a broad species-level phylogenetic hypothesis for Bjerkandera in the Neotropics and worldwide and to discuss the taxonomic status and diversity of the species in this genus. This study is based on a morphological examination of specimens collected between 2012 and 2017, and on a revision of original collections, including the type specimens. A total of eleven ITS and seven nLSU sequences were generated and phylogenetic analyses based on Bayesian Inference (BI) and Maximum Likelihood (ML) were performed. An extensive documentation of the species diversity within Bjerkandera in the Neotropics is presented. Genetic data of B. mikrofumosa were obtained for the first time and its phylogenetic position was tested. Additionally, its geographic distribution was extended in the Neotropics to Argentina and Brazil. Finally, molecular and morphological evidence was used to propose a new species for the genus, Bjerkandera albocinerea sp. nov. This study provides an update of the known diversity of the genus in the Neotropics and worldwide. In addition, our results indicate that the number of taxa in Bjerkandera has been underestimated by morphological evidence, and may actually be greater than traditionally accepted.